The New India Progress Through Democracy - Planning Commission (Planning Commission, 1956)
India’s Second Five Year Plan is designed to lift the Indian economy and the Indian people forward, and speed the rebirth of India as a modern nation. The Plan’s immediate aims are economic and social—to raise living standards, to increase national income, production and employment, to provide a richer and fuller life, to break further through the barrier of poverty which has held the Indian people and the Indian economy stagnant in a swiftly developing world.
Planning Commission Government of India
Planning Commission Government of India